ClojureScript : up and running - Sierra, Stuart (O'Reilly, 2012)
Learn how to build complete client-side applications with ClojureScript, the Clojure language variant that compiles to optimized JavaScript. This hands-on introduction shows you how ClojureScript not only has similarities to JavaScript--without the flaws--but also supports the full semantics of its parent language. You'll delve into ClojureScript's immutable data structures, lazy sequences, first-class functions, macros, and support for JavaScript libraries. No previous experience with Clojure or ClojureScript is necessary. If you're familiar with JavaScript, HTML, CSS, and the DOM, you'll quickly discover that ClojureScript has the same reach as JavaScript, but with more power. Start writing ClojureScript code with the Leiningen build system Learn how the ClojureScript compiler works to produce optimized JavaScript Use JavaScript functions and libraries directly from ClojureScript code Explore functions in Clojure's sequence library such as map, reduce, and filter Use macros to define new control structures or embed domain-specific languages Compile manually or script your own workflow with ClojureScript's compiler tools Integrate ClojureScript with Clojure on the JVM to build powerful client-server applications.